METODOLOGI pengajaran agama Islam - DEPARTEMEN AGAMA REPUBLIK INDONESIA (Depag RI. Proyek Pembinaan PTA, 1982)
ir,c.1/tr. c.2/tr,c.3/wk, c.4/tr,c.4/tr,c.5/tr,c.6-7/why, c.8/why, c.9-10/en, c.11-12/en, c.13/wk, c.14